Chemotherapy and target therapy as neo-adjuvant approach for initially unresectable colorectal liver metastases - Luigi Rossi; Angelo Zullo; Federica Zoratto; Anselmo Papa; Martina Strudel; Maria Colonna; Silverio Tomao (Oncology Reviews, 2012)
Although surgery is the most effective treatment for liver metastases in colorectal cancer patients, only 15-20% of these patients are suitable for a radical surgical approach, and metastases recurrence may occur at follow up. In the last decade, the use of pre-operative chemotherapy in combination with new biological drugs has been introduced. We reviewed data of neo-adjuvant chemotherapy strategies aimed at increasing the resection rate of liver metastases in colorectal cancer patients who were initially considered unresectable.